The Transition of Lauw Ping Nio’s Portrait (Nyonya Meneer) from the Jamu Cap Nyonya Meneer brand to the Minyak Telon brand owned by PT Bhumi Empon Mustiko due to Bankruptcy of PT Perindustrian Nyonya Meneer - Ardinovan Junico Alief; Parulian Paidi Aritonang (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to analyze Intellectual Property Rights, particularly Trademark Rights, as a form of protection for individuals who create creative works. This research uses a doctrinal approach in the field of law. The data is collected through qualitative analysis. This analysis focuses on the transition of the Lauw Ping Nio Portrait (Nyonya Meneer) from the “Jamu Cap Nyonya Meneer” brand to the “Minyak Telon” brand owbned by PT Bhumi Empon Mustiko. The results of this study conclude that the transition is legally valid, based on the state of bankruptcy of PT Nyonya Meneer.